Evidence-based decision-making for vaccine introductions: Overview of the ProVac International Working Group's experience. (7th May 2015) - Jauregui, Barbara; Garcia, Ana Gabriela Felix; Bess Janusz, Cara; Blau, Julia; Munier, Aline; Atherly, Deborah; Mvundura, Mercy; Hajjeh, Rana; Lopman, Benjamin; Clark, Andrew David; Baxter, Louise; Hutubessy, Raymond; et al.
Highlights: This article is an introductory overview of the International Working Group (IWG). IWG supported regional workshops and vaccine economic evaluations in Africa, Eastern Mediterranean and Europe. Many developing countries are moving away from donor funding and need to assess value for money. ProVac's method can be implemented successfully outside of Latin American and the Caribbean. Abstract: Introduction: Pan American Health Organization's (PAHO) ProVac Initiative aims to strengthen countries' technical capacity to make evidence-based immunization policy. With financial support from the Bill and Melinda Gates Foundation, PAHO established the ProVac International Working Group (IWG), a platform created for two years to transfer the ProVac Initiative's tools and methods to support decisions in non-PAHO regions. Methods: In 2011, WHO Regional Offices and partner agencies established the IWG to transfer the ProVac framework for new vaccine decision support, including tools and trainings to other regions of the world. During the two year period, PAHO served as the coordinating secretariat and partner agencies played implementing or advisory roles. Results: Fifty nine national professionals from 17 countries received training on the use of economic evaluations to aid vaccine policy making through regional workshops. The IWG provided direct technical support to nine countries to develop cost-effectiveness analyses to inform decisions. All nine countries introduced the new vaccine evaluated or their NITAGs have made a recommendation to the Ministry of Health to introduce the new vaccine. Discussion: Developing countries around the world are increasingly interested in weighing the potential health impact due to new vaccine introduction against the investments required. During the two years, the ProVac approach proved valuable and timely to aid the national decision making processes, even despite the different challenges and idiosyncrasies encountered in each region. The results of this work suggest that: (1) there is great need and demand for technical support and for capacity building around economic evaluations; and (2) the ProVac method of supporting country-owned analyses is as effective in other regions as it has been in the PAHO region. Conclusion: Decision support for new vaccine introduction in low- and middle-income countries is critical to guiding the efficient use of resources and prioritizing high impact vaccination programs.